Neurotic perfectionism and general self-efficacy among a sample of talented high school students in Jeddah - Al-Jehani, Jowana Abdullah; Al-Dhabiban, Nawal Abdullah (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the relationship between perfectionism and general self-efficacy among a sample of talented students in high school in Jeddah, and to identify the level of perfectionism and general self-efficacy, as well as to identify the differences according to gender. The study sample consisted of (50) male and (50) female talented students at the secondary level. The descriptive correlative approach was used to verify the hypotheses of the study. The researcher applied the perfectionism scale for university youth prepared by Samira Shend (2017), and The General Self-Efficacy Scale prepared by (Sherer et al, 1982) and translated by Nihad Mahmoud (2016). The results showed an average level of perfectionism, a high level of general self-efficacy, and a statistically significant relationship between perfectionism and general self-efficacy in the study sample. In addition to the absence of differences in perfectionism as well as general self-efficacy due to the gender variable. The researcher recommends to raise awareness of mental disorders such as perfectionism, its negative impact, and ways to prevent it among talented students. And the need to maintain a high level of general self-efficacy, which contributes in improving mental health.